Implementasi Pembelajaran E-Learning PAI Era Pandemi Covid-19 - Wasito Wasito; Achmad Rikza Zakaria (Permata : Jurnal Pendidikan Agama Islam, 2022)
This research is about to discuss about E-learning of Islamic religious education subjects in the era of the Covid-19 pandemic. The beginning of 2020 spread a dangerous virus, namely Covid-19. The Covid-19 virus has changed all education systems at all levels, and learning activities carried out face-to-face must be replaced with online learning. During the Covid-19 pandemic, PAI teachers at SMKN I Semen Kediri carried out creativity and innovation in learning. Teachers can use learning media such as WhatsApp media, YouTube, PowerPoint, google web on the internet. This study was conducted at SMKN I Semen Kediri Regency, the goal to be achieved, namely the implementation of E-learning on PAI subjects in SMKN I Semen Kediri, and the constraints on the implementation of E-learning on PAI subjects in the Covid-19 pandemic era at SMKN I Semen Kediri. This study is a qualitative research using data collection methods, observation, interviews and documentation. The findings of this study resulted in; first, the implementation of e-learning learning in PAI subjects at SMKN I Semen Kediri by utilizing technology. Among them using WhatsApp media, YouTube media, Google Internet media, Google Classroom, and materials made by yourself with PowerPoint media. Online learning has advantages including it has become a trend today, namely the millennial era, in the era of 4.0, and learning that is not limited to space and time. Second, the obstacles experienced by PAI teachers in terms of delivering material to students, namely the use of the internet network, the lack of understanding of teachers to internet tools, the experience of teaching teachers to deal with changing situations that are usually done face to face.Keyword: Learning; E-learning; Covid-19 Pandemic. Abstrak Penelitian ini hendak membahas tentang pembelajaran e-learning mata pelajaran pendidikan agama Islam pada era pandemi Covid-19. Awal tahun 2020 merebak virus yang berbahaya, yakni Covid-19. Adanya virus Covid-19 merubah semua sistem pendidikan dari segala jenjang, serta kegiatan pembelajaran yang dilaksanakan secara tatap muka harus digantikan dengan pembelajaran online. Dalam masa pandemi Covid-19, guru PAI di SMKN I Semen Kediri melakukan kreativitas dan inovasi di dalam pembelajaran. Guru dapat menggunakan media pembelajaran seperti media WhatsApp, YouTube, PowerPoint, google web pada internet. Penelitian ini dilakukan di SMKN I Semen Kabupaten Kediri, tujuan yang ingin dicapai, yakni mengenai pelaksanaan pembelajaran e-learning pada mata pelajaran PAI yang ada di SMKN I Semen Kediri, dan kendala implementasi pembelajaran e-learning pada mata pelajaran PAI era Pandemi Covid-19 di SMKN I Semen Kediri. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode pengumpulan data, observasi, wawancara dan dokumentasi. Temuan penelitian ini menghasilkan; Pertama, pelaksanaan pembelajaran e-learning pada mata pelajaran PAI di SMKN I Semen Kediri dengan memanfaatkan teknologi. Diantaranya menggunakan media WhatsApp, media Youtube, media Google Internet, Google Classroom, dan materi yang dibuat sendiri dengan media PowerPoint. Pembelajaran online punya keunggulan diantaranya sudah menjadi tren dimasa kini, yakni era milenial, di era 4.0, dan pembelajaran yang tidak terbatas pada ruang dan waktu. Kedua, kendala yang dialami guru PAI dalam hal menyampaikan materi kepada siswa, yaitu ada pada penggunaan jaringan internet, kurangnya pemahaman guru terhadap tools internet, pengalaman mengajar guru untuk menghadapi perubahan situasi yang biasanya dilakukan tatap muka.Kata Kunci: Pembelajaran; E-learning; Pandemi Covid-19.